Data for: A Digital Twin for supporting decision-making and stakeholder collaboration in urban decarbonization processes. A participatory development in Gothenburg. - Thuvander, Liane; Maiullari, Daniela; Dokter, Giliam (Chalmers University of Technology, 2024)
The dataset contains questionnaire survey data from the evaluation of a Digital Twin Viewer (CDTE) for the city of Gothenburg. The questionnaire collects background information about the users and their familiarity with digital twins or other digital tools, their evaluation of the usability and usefulness of the City Digital Twin and general reflections on the characteristics and the maintenance of the viewer platform.

Data is collected through two assessment workshops: First, a workshop with 22 stakeholders representing the city energy provider, the planning and environmental department of the municipality, property companies both municipal and private, and researchers; and second, a workshop with 70 master students with a background in architecture and urban planning as part of a course on sustainable development and stakeholder engagement.

Datafilen innehåller från enkätundersökningen som utvärderar en Digital Twin Viewer (CDTE) som har utvecklats för staden Göteborg. Enkäten samlar in bakgrundsinformation om användarna och deras förtrogenhet med digitala tvillingar eller andra digitala verktyg, deras utvärdering av användbarheten och användbarheten av CDTE och allmänna reflektioner kring plattformens egenskaper och underhåll.

Data samlades in genom två utvärderingsworkshops: en workshop med 22 intressenter som representerar stadens energileverantör, plan- och miljöavdelningen i kommunen, fastighetsbolag (både kommunala och privata) samt forskare; och en workshop med 70 masterstudenter med bakgrund inom arkitektur och stadsplanering.
Data for: A Digital Twin for supporting decision-making and stakeholder collaboration in urban decarbonization processes. A participatory development in Gothenburg.
Keywords: Cadastral parcels; Fastighetsområden; Energy resources; Energiresurser; Environmental monitoring facilities; Anläggningar för miljöövervakning; digital twin; digital tvilling; stakeholders; intressenter; building stock; byggnadsbestånd; urban energy; urban energi; decision making; beslutsfattning; Community, urban and rural life; Lokalsamhälle, stads- och landsbygdsliv; Civil Engineering; Samhällsbyggnadsteknik; Architectural Engineering; Arkitekturteknik; Energy Systems; Energisystem; Environmental Management; Miljöteknik och miljöledning; Planning / Cadastre; Fastigheter och fysisk planering; Geoscientific Information; Geovetenskap; Environment; Miljö; Location; Positionering; Society; Samhälle och kultur